2021
DOI: 10.31083/j.rcm2202041
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and cardiovascular system—a comprehensive review

Abstract: Coronavirus disease 2019 (COVID-19), a mystified cryptic virus has challenged the mankind that has brought life to a standstill. Catastrophic loss of life, perplexed healthcare system and the downfall of global economy are some of the outcomes of this pandemic. Humans are raging a war with an unknown enemy. Infections, irrespective of age and gender, and more so in comorbidities are escalating at an alarming rate. Cardiovascular diseases, are the leading cause of death globally with an estimate of 31% of death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 74 publications
(113 reference statements)
0
9
0
Order By: Relevance
“…A case–control study conducted with patients admitted to a hospital in Madrid, (Spain) due to COVID-19 during the first wave of the pandemic showed that pre-existing hypertension was associated with a greater number of Long COVID symptoms ( 47 ). During the acute phase of COVID-19, patients with cardiovascular diseases, including hypertension, had a higher risk of worsening clinical conditions and death from COVID-19 ( 48 ). This situation occurs potentially because there is an exacerbated pro-inflammatory response (e.g., cytokine storm) associated with the SARS-CoV-2 infection in people with hypertension mediated by the angiotensin-converting enzyme 2 (ACE2) receptor ( 47–49 ).…”
Section: Discussionmentioning
confidence: 99%
“…A case–control study conducted with patients admitted to a hospital in Madrid, (Spain) due to COVID-19 during the first wave of the pandemic showed that pre-existing hypertension was associated with a greater number of Long COVID symptoms ( 47 ). During the acute phase of COVID-19, patients with cardiovascular diseases, including hypertension, had a higher risk of worsening clinical conditions and death from COVID-19 ( 48 ). This situation occurs potentially because there is an exacerbated pro-inflammatory response (e.g., cytokine storm) associated with the SARS-CoV-2 infection in people with hypertension mediated by the angiotensin-converting enzyme 2 (ACE2) receptor ( 47–49 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the pathophysiology of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is characterized by the overproduction of inflammatory cytokines (such as IL-6 and TNF-α) leading to systemic inflammation and multiple organ dysfunction syndrome, including acute and chronic effects on the cardiovascular system ( AlShahrani et al, 2021 ). In addition, preliminary studies indicate that vascular endothelial cells can be infected by SARS-CoV-2, and evidence of widespread endothelial injury and inflammation is found in severe patients with COVID-19 ( Nagele et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed that the presence of comorbidities increases the risk of death due to COVID-19 [ 3 , 5 , 6 , 29 , 30 ]. In our analysis, the clinical predictors of all-cause death were age, which has already been established as one of the most crucial factors facilitating survival in COVID-19, and chronic kidney disease [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was estimated that approximately 2% of the overall population with SARS-CoV-2 infection would eventually require hospitalization and oxygen therapy [ 2 ]. In recent months, the predictors of worse outcomes, such as age and the presence of severe chronic comorbidities, including cardiovascular and pulmonary diseases, were defined [ 3 , 4 , 5 , 6 ]. Biomarkers, such as neutrophile-to-lymphocyte ratio and interleukin-6, were established as independent predictors of COVID-19 worsening, although their evaluation was not possible until the blood sample was taken [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%